Does Postoperative Anticoagulation Therapy Lead to a Higher Success Rate for Microvascular Free-Tissue Transfer in the Head and Neck? A Systematic Review and Meta-Analysis - Liu, Jinglong; Shi, Quan; Yang, Shuo; Liu, Bo; Guo, Bin; Xu, Juan (Journal of Reconstructive Microsurgery, 2018)
Background Due to limited evidence, it is unclear whether postoperative anticoagulation therapy may lead to higher success rates for microvascular free-flap surgery in the head and neck. This review evaluated whether postoperative anticoagulation therapy can lead to a better result in head and neck reconstruction.Methods PubMed, Embase, and the Cochrane Library were used to search for articles on the efficacy of postoperative antithrombotic therapy in free-flap transfer during head and neck reconstruction without language restrictions in February of 2017. A random-effects model was used to estimate the relative risk ratio (RR) with 95% confidence intervals (CIs). The measured outcomes were flap loss, thromboembolic events, and hematoma formation.Results A total of 2,048 free-flap surgery procedures in the head and neck were analyzed. There was no significant difference in the occurrence of flap loss and thromboembolic events in the anticoagulation group compared with the nonanticoagulation group (RR = 1.25, 95% CI = 0.85–1.81, p = 0.26; and RR = 1.05, 95% CI = 0.74–1.48, p = 0.79, respectively). The risk of hematoma was twice as high in the anticoagulation group than the nonanticoagulation group, which was statistically significant (RR = 2.02, 95% CI = 1.08–3.76, p = 0.03).Conclusion The findings from our meta-analysis indicate that postoperative anticoagulation therapy barely decreases the risks of flap loss and thromboembolic events in free-flap surgery in the head and neck. However, it may significantly increase the risk of hematoma formation. Considering the limitations of this meta-analysis, additional high-quality, multicenter, prospective, randomized controlled studies are needed to confirm these findings.
Keywords: anticoagulation; free flap; head and neck